Industrial waste characterization and management in Arasanj industrial estate, Iran - Hamed Mazandaranizadeh; Ali Koolivand; Mohammad Binavapoor; Fatollah Gholami Borujeni; Reza Darvishi Cheshmeh Soltani (Kuwait Journal of Science)
The aim of this study was to survey the total waste generation and characterization as well as the related management activities in Arasanj industrial estate. In the first step, all the industrial processes, the types and quantities of products, waste generation and management and other general data were obtained by means of a structured questionnaire. In the next step, 15 industries were selected and their wastes were sorted by hand and then weighed. In addition, detailed information about the waste in all industries was identified through interviews and observations. The results showed that total waste generation in Arasanj was 1002.55 Kg day-1. Organic waste and metals constituted 64% of total waste generated and all other components were responsible for 36% of this amount. It was also indicated that the majority of industrial wastes come from food and beverage industries (46%), metallic industries (26.3%) and chemical industries (10.4%). Based on the results, total hazardous waste accounts for nearly 14.29% of total waste generated. The management of industrial waste in Arasanj industrial estate was weak and a variety of waste management problems were identified. For the best management, recycling and reuse of industrial wastes should be implemented as much as possible.